BUDAYA KERJA APARATUR PEMERINTAH DI KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Reha Sunjani; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed to determine the behavior of Administrative Pemrintah work culture in Bukit Batu subdistrict Bengkalis. This study focused on the performance of the government in Kecamtan Aparutur Bukit Batu to the ministry. Based on the background of the problem, the study aims to identify and analyze the behavior of Government Personnel Work culture in Bukit Batu subdistrict Bengkalis. The research method is qualitative, with the technique of collecting data through observation, interviewing and documents .The results of the field studies showed that the behavior of the work culture of government officials in Bukit Batu subdistrict is not going well, the government apparatus in Bukit Batu subdistrict performance undisciplined, because the maintenance in the process of exchange of letters did not go as timely or efficient. aside from the lack of discipline permaslahan that is in the performance of the Government apparatus was the lack of friendliness in the waiters to the people in the district of Bukit Batu Bengkalis regency, and aside from the lack of awareness of the Apparatus of the societal conditions. This makes the problem so that the government apparatus is not capable of being a good guideline for people in the District Bukit Batu Bengkalis.Keywords: Work Culture, Government Personnel